Why sustainable, inclusive, and resilient investment makes for efficacious post‐COVID medicine. (9th June 2021) - Zenghelis, Dimitri
Abstract: The global economy is facing an unprecedented challenge, with the risk of a protracted depression following the response to COVID‐19. In 2014, I argued here that macroeconomic conditions made it a relatively favorable time to kick‐start investments in a resource‐efficient, low carbon economy. Yet the opportunity was, for the most part, squandered. Failure to utilize active fiscal policy contributed to growing private indebtedness, limited productivity and wage growth and widened inequality helping erode trust in institutions. All the while, greenhouse gas emissions continued to rise. This time, there are grounds for optimism that a more coordinated response toward generating an ambitious transition to net zero emissions might contribute to a strong, sustainable, and resilient recovery. This article is categorized under: Climate Economics > Economics of Mitigation Abstract : A key reason for the decline in both private investment and global productivity since the crash of 2008 has been the neglect of infrastructure investment. We now have an opportunity to utilise fiscal policy to channel private savings and drive a zero‐carbon and climate‐resilient global economy.